Torompio Dance, 1943-2000: Identity, Adaptation, and Cultural Heritage in Poso - Nesika, Varischa Anugra; Windayanti, Windayanti; Mutawakkil, Mutawakkil; Nuraedah, Nuraedah (Universitas Pahlawan Tuanku Tambusai, 2025)
This research was carried out in Bo'e village, South Pamona District, Poso Regency by discussing 3 things, namely: First: The role of Torompio dance as a reinforcement of the cultural identity of the Poso community. Second: A form of adaptation of the Torompio dance that occurred in the period 1943-2000. Third, Torompio dance cultural heritage in Poso Regency. This study aims to examine the Torompio Dance as a form of identity, a form of adaptation, and a means of cultural inheritance of the Poso people in the period 1943–2000. The Torompio Dance is one of the traditional dances of the Pamona Tribe in Central Sulawesi that has strong symbolic and social value, especially in the context of traditional events, harvest thanksgiving, and welcoming guests. This research uses historical methods with the stages of Heuristic, Source Criticism, Interpretation, and Historiography. Data was obtained through literature studies, observations, interviews, and documentation in Bo'e Village, South Pamona District, Poso Regency. The results of the study show that the Torompio Dance functions as a reinforcement of the cultural identity of the Poso people through the symbolization of movements that represent the meeting between men and women. This dance has also undergone adaptations in terms of music, fashion, and various forms of performance in response to globalization. The process of inheriting the Torompio Dance takes place through two main paths: socialization in the family and community environment, as well as enculturation through training in the studio and participation in traditional events representing the sustainability/survival of Torompio dance in the present and future as a reinforcement of Identity, Adaptation and Cultural Heritage.